Reliability Assessment of Bangla Version of the Shoulder Pain and Disability Index (SPADI) - Yousuf, Mohammad (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 145